Simultaneous estimation of rabeprazole and diclofenac sodium in tablet dosage form by RP-HPLC method - Jogu Chandrudu; Srikanth Choudary Pallothu (International Journal of Pharmacy and Analytical Research, 2022)
A novel, simple, selective, rapid, precise and accurate reverse phase high pressure liquid chromatographic method has been developed for the simultaneous estimation of diclofenac sodium and rabeprazole sodium from pharmaceutical formulations. The method was developed using a Inertsil - C18, ODS column column with a mobile phase el carried out at 210 nm. The developed method was validated for linearity, accuracy, precision, limit of detection and limit of quantization. The proposed method can be used for the estimation of these drugs in combined dosage forms.